EXPLORING SCHOOL SAFETY MANAGEMENT CHALLENGES AND INTERVENTIONS: A CASE STUDY OF A SECONDARY SCHOOL IN SOUTH AFRICA - Mokoena, Ntabiseng; Kimanzi, Mathew Kimweli (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2024)
Secondary schools in South Africa, encounter numerous safety dilemmas, including incidents of harassment and the widespread influence of gang-related conduct. In South Africa, gang-related abuse constitutes a significant societal challenge, affecting over 15% of the population, particularly impacting the youth demographic. Despite acknowledgment of these challenges, gaps exist between the recognition of such safety issues and the execution and efficacy of safety management measures in these settings. This study was conducted to investigate the obstacles and interventions pertaining to the management of safety within the framework of a secondary school in South Africa. The investigation utilized a qualitative methodology within a case study framework, using a sample of 30 participants. These consisted of teachers, the school principal, learners and members of the School Governing Body (SGB). Data was collected through focus group interviews and analysed primarily using thematic analysis. The study found out that factors that were inhibiting school safety were lack of resources, in-effective school safety personnel, lack of adherence to safety protocols and obsolete safety policies and culture. It is recommended that that the formation of a safety policy committee is indispensable for enhancing the school's capacity to document and manage safety incidents.